Aridity exacerbates grazing‐induced rangeland degradation: A population approach for dominant grasses. Issue 10 (9th July 2020) - Oñatibia, Gastón R.; Amengual, Gerónimo; Boyero, Luciano; Aguiar, Martín R.
Abstract: The current human‐induced intensification of grazing pressure and the aridity increase as a result of climate change are unprecedented and have been identified as the main drivers that cause desertification in rangelands world‐wide. In these ecosystems, human well‐being mostly depends on plant species that provide forage for domestic herbivores. However, scarce evidence exists about the interaction between regional aridity level and human‐induced disturbances as determinants of forage plant populations' structure and dynamics. We studied the effects of domestic grazing intensification on the population structure of dominant native grasses, in three rangeland sites located across a regional aridity gradient: a semi‐desert (high‐aridity site), a shrub–grass steppe (intermediate‐aridity site) and a grass steppe (low‐aridity site). We also studied the effect of 2‐year grazing exclusion on the growth of defoliated plants of a key native forage grass species common to the three sites. Grazing decreased total grass density and increased the frequency of small plants in all sites, particularly for forage species. However, the size of the grazing intensification effect was the greatest in the high‐aridity site, where intensive grazing produced a ten‐fold reduction of grass density. Moreover, defoliated plants recovery (growth) was lower as aridity increased. Synthesis and applications . Our study provides evidence of a negative synergistic effect of grazing pressure and aridity that may lead to the collapse of grass populations. Long‐term grazing intensification degrades the population structure of grasses, particularly in high‐aridity sites, where the forage provision is substantially reduced. These results refute the hypothesis that plant traits of dominant species adapted to high aridity allow them to resist herbivory. Besides, high aridity delays plant recovery after defoliation (low resilience). The management of both grazing pressure and the length of grazing rest according to ecological‐site aridity are key aspects for maintaining the forage provision of rangelands. Monitoring plant populations' structure through time and space strengthens inferences about responses of forage species to ongoing changes in disturbance and stress regimes. This knowledge is complementary to regional and world‐wide monitoring endeavours based on land cover, and it contributes to the robust design of sustainable management of global rangelands. Abstract : Our study provides evidence of a negative synergistic effect of grazing pressure and aridity that may lead to the collapse of grass populations. Long‐term grazing intensification degrades the population structure of grasses, particularly in high‐aridity sites, where the forage provision is substantially reduced. These results refute the hypothesis that plant traits of dominant species adapted to high aridity allow them to resist herbivory. Besides, high aridity delays plant recovery after defoliation (low resilience). The management of both grazing pressure and the length of grazing rest according to ecological‐site aridity are key aspects for maintaining the forage provision of rangelands. Monitoring plant populations' structure through time and space strengthens inferences about responses of forage species to ongoing changes in disturbance and stress regimes. This knowledge is complementary to regional and world‐wide monitoring endeavours based on land cover, and it contributes to the robust design of sustainable management of global rangelands. Resumen: La intensificación de la presión de pastoreo y el aumento de la aridez como resultado del cambio climático no tienen precedentes y se han identificado como las principales causas de desertificación en los ecosistemas pastoriles de todo el mundo. En estos ecosistemas, el bienestar humano depende principalmente de las especies de plantas que proveen forraje para los herbívoros domésticos. Sin embargo, se conoce poco sobre la interacción entre el nivel de aridez regional y los disturbios inducidos por los humanos como determinantes de la estructura y dinámica de las poblaciones de plantas forrajeras. Estudiamos cómo la intensificación del pastoreo doméstico afecta la estructura de las poblaciones de pastos nativos dominantes, en tres sitios ubicados a lo largo de un gradiente de aridez regional: un semi‐desierto (alta aridez), una estepa arbustivo‐graminosa (aridez intermedia) y una estepa graminosa (baja aridez). También estudiamos el crecimiento de plantas defoliadas de una especie forrajera común en los tres sitios. El pastoreo disminuyó la densidad total de pastos y aumentó la frecuencia de plantas pequeñas en todos los sitios, particularmente para especies forrajeras. Sin embargo, el tamaño del efecto de la intensificación del pastoreo fue mayor en el sitio de alta aridez, donde el pastoreo intensivo diezmó la densidad de pastos. El crecimiento de plantas defoliadas (recuperación) fue menor a medida que aumentó la aridez. Síntesis y aplicaciones . Nuestro estudio muestra la existencia de un efecto sinérgico negativo de la presión de pastoreo y la aridez que puede conducir al colapso de las poblaciones de pastos. La intensificación del pastoreo degrada la estructura poblacional de los pastos, particularmente en sitios con alta aridez, donde la provisión de forraje se reduce sustancialmente. Estos resultados refutan la hipótesis que establece que los rasgos de las especies adaptadas a la alta aridez les permiten resistir la herbivoría. Además, la mayor aridez retrasa la recuperación de las plantas defoliadas (baja resiliencia). El manejo de la presión de pastoreo y la duración de los descansos al pastoreo acordes con la aridez de cada sitio ecológico son aspectos críticos para mantener la provisión de forraje. El monitoreo de la estructura de las poblaciones en el tiempo y el espacio fortalece las inferencias sobre las respuestas de las especies forrajeras a los cambios que están ocurriendo en los regímenes de disturbio y estrés. Este conocimiento contribuye al diseño robusto del manejo sostenible de los ecosistemas pastoriles.